2008
DOI: 10.1160/th07-10-0603
|View full text |Cite
|
Sign up to set email alerts
|

Slight differences in sulfation of algal galactans account for differences in their anticoagulant and venous antithrombotic activities

Abstract: We compared sulfated galactans (SGs) from two species of red algae using specific coagulation assays and experimental models of thrombosis. These polysaccharides have an identical saccharide structure and the same size chain, but with slight differences in their sulfation patterns. As a consequence of these differences, the two SGs differ in their anticoagulant and venous antithrombotic activities. SG from G. crinale exhibits procoagulant and prothrombotic effects in low doses (up to 1.0 mg/kg body weight), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 25 publications
1
69
0
5
Order By: Relevance
“…Mais recentemente, FONSECA et al (2008) compararam galactanas sulfatadas de B. occidentalis e G. crinale. Suas diferenças nas proporções e/ou distribuição dos radicais sulfato na estrutura química com seus mecanismos distintos de interação com proteases, inibidores e ativadores do sistema de coagulação, produziram atividades anti-e pró-coagulantes, além de anti-e pró-trombóticas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Mais recentemente, FONSECA et al (2008) compararam galactanas sulfatadas de B. occidentalis e G. crinale. Suas diferenças nas proporções e/ou distribuição dos radicais sulfato na estrutura química com seus mecanismos distintos de interação com proteases, inibidores e ativadores do sistema de coagulação, produziram atividades anti-e pró-coagulantes, além de anti-e pró-trombóticas.…”
Section: Resultsunclassified
“…FARIAS et al (2000) e PEREIRA et al (2005) relataram PS isolados das algas Botryocladia occidentalis e Gelidium crinale (Rhodophytas) com propriedades anticoagulantes. Esses PS também expressam ações anti-e pró-trombóticas, quando utilizados em modelos experimentais de trombose em ratos (FONSECA et al, 2008). A rodofícea Halymenia pseudofloresia possui PS com atividade anticoagulante superior a HEP (RODRIGUES et al, 2009).…”
Section: Introductionunclassified
“…These studies suggested that was interesting to investigate this class of macromolecules in animal models (Mourão and Pereira, 1999;Farias et al, 2001;Zhang et al, 2003;Assreuy et al, 2008;Fonseca et al, 2008;Lins et al, 2009;Ananthi et al, 2010), as valuable tools on development of new pharmacological drugs. The anticoagulant activity of marine algae SPs has been widely reported.…”
Section: Biological Assaysmentioning
confidence: 99%
“…Talarico et al (2004) reported that the sulfated galactans obtained from red seaweeds Gymnogongrus griffithsiae and Cryptonemia crenulata showed antiviral properties against four serotypes of dengue virus in different host cell types. Fonseca et al (2008), investigating the effects of a SP isolated from Gelidium crinale (Rhodophyta) on a venous thrombosis model, reported that it could be considered as a valuable tool for better comprehension of the physiopathology of thromboembolic diseases. A SP isolated from the red marine algae Champia feldmannii demonstrated to be an important edematogenic agent (Assreuy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The galactan of G. crinale was shown to present anticoagulant effect, as it inhibits thrombin and factor Xa by antithrombin and heparin cofactor II. It also presents antithrombotic effect via inhibition of venous and arterial thrombosis in rats (Pereira et al, 2005;Fonseca et al, 2008). However, its inflammatory role was not described yet.…”
Section: Short Communicationmentioning
confidence: 99%